TEACHER STRATEGIES IN TEACHING ENGLISH ONLINE DURING PANDEMIC IN INDONESIAN SECONDARY EDUCATION - Rizqa Amaliah; Munir Munir; Muh. Tahir (Universitas Negeri Makassar, 2022)
This study aims to describe teachers’ strategies in teaching English online during the pandemic. The researchers applied qualitative methods to achieve the research objectives, the data collected in this research were in the form of interviews. The subjects of this study were English teachers at SMP NEG. 1 Mappakasunggu and SMP NEG. 1 Mangarabombang. The interview sample was 8 teachers. In this study, researchers analyzed the data by understanding, compiling codes, looking for themes, and drawing conclusions. Based on the results of the study, the researchers found that teachers' strategies in teaching English online during a pandemic are discussion, independent learning, small group work, project and collaborative learning. Although choosing learning media is the most important thing for online learning success, teachers also try their best to convey the learning material well.